The underrepresentation of female participants in studies assessing the impact of high-dose exercise on cardiovascular outcomes: a scoping review. (11th May 2021) - Pallikadavath, S; Patel, R; Kemp, CL; Hafejee, M; Peckham, N; Jain, V; Mccann, GP
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cardiovascular adaptations as a result of exercise conducted at high-intensity and high-volume are often termed the 'Athlete's heart'. Studies have shown that these cardiovascular adaptations vary between sexes. It is important that both sexes are well represented in this literature. However, many studies assessing the impact of high-dose exercise on cardiovascular outcomes under-recruit female participants. Purpose: This scoping review aimed to evaluate the representation of females in studies assessing the impact of high-dose exercise on cardiovascular outcomes and demonstrate how this has changed over time. Methods: The scoping review protocol as outlined by Arksey and O'Malley was used. OVID and EMBASE databases were searched and studies independently reviewed by two reviewers. Studies must have investigated the effects of high-dose exercise on cardiovascular outcomes. To assess how the recruitment of females has changed over time, two methods were used. One, the median study date was used to categorise studies into two groups. Two, studies were divided into deciles to form ten equal groups over the study period. Mean percentage of female recruitment and percentage of studies that failed to include females were calculated. Results: Overall, 250 studies were included. Over half the studies (50.8%, n = 127) did not include female participants. Only 3.2% (n = 8) did not include male participants. Overall, mean percentage recruitment was 18.2%. The mean percentage of recruitment was 14.5% before 2011 and 21.8% after 2011. The most recent decile of studies demonstrated the highest mean percentage of female recruitment (29.3%) and lowest number of studies that did not include female participants (26.9%). Conclusion: Female participants are significantly underrepresented in studies assessing cardiovascular outcomes caused by high-dose exercise. The most recent studies show that female recruitment may be improving, however, this still falls significantly short for equal representation. Risk factors, progression and management of cardiovascular diseases vary between sexes, hence, translating findings from male dominated data is not appropriate. Future investigators should aim to establish barriers and strategies to optimise fair recruitment.